Achieving Pareto-Optimality: Invisible Hands, Social Contracts, and Rational Deliberation - Gauthier, David; Justus Liebig University Giessen (My University, 2013)
I begin with two simple, similar interactions. In one, maximizing agents will reach a Pareto-optimal equilibrium, in the other, they won't. The first shows the working of the Invisible Hand; the second, its limitations. Using other simple interactions in which equilibrium and P-optimality are incompatible, I argue that the rational outcome of interaction answers to optimality rather than maximization, and requires agents to cooperate in realizing an agreed outcome, rather than to seek their best reply to their fellows. The terms of cooperation are set by a social contract, which coordinates choices to achieve a Pareto-optimum when the Invisible Hand is absent.
Keywords: best-reply; equilibrium; Invisible Hand; maximization; Pareto-optimality; rational choice; ddc:100; ddc:330